Methodology for post-event analysis of flash floods – Svacenický Creek case study - BLAŠKOVIČOVÁ, Lotta; HORVÁT, Oliver; HLAVČOVÁ, Kamila; KOHNOVÁ, Silvia; SZOLGAY, Ján (Contributions to Geophysics and Geodesy, 2011)
In this paper a methodology for a post-event analysis of a flash flood andestimation of the flood peak and volume are developed and tested. The selected flash floodoccurred on the 6th of June, 2009 in the Svacenický Creek Basin. To understand rainfallrunoffprocesses during this extreme flash flood, the runoff response was simulated usingthe spatially-distributed hydrological model KLEM (Kinematic Local Excess Model). Thedistributed hydrological model is based on the availability of raster information about thelandscape’s topography, soil and vegetation properties and radar rainfall data. In themodel, the SCS-Curve Number procedure is applied to a grid for the spatially-distributedrepresentation of the runoff-generating processes. A description of the drainage system’sresponse is used to represent the runoff’s routing. The simulated values achieved by theKLEM model were comparable with the maximum peak estimated on the basis of thepost-event surveying. The consistency of the estimated and simulated values from theKLEM model was evident both in time and space, and the methodology has shown itspractical applicability.